Introduction: University Collegiality and the Erosion of Faculty Authority - Kerstin Sahlin; Ulla Eriksson-Zetterquist (Emerald Publishing Limited, 2023)
Recent changes in university systems, debates on academic freedom, and changing roles of knowledge in society all point to questions regarding how higher education and research should be governed and the role of scientists and faculty in this. Rationalizations of systems of higher education and research have been accompanied by the questioning and erosion of faculty authority and challenges to academic collegiality. In light of these developments, we see a need for a more conceptually precise discussion about what academic collegiality is, how it is practiced, how collegial forms of governance may be supported or challenged by other forms of governance, and finally, why collegial governance of higher education and research is important. We see collegiality as an institution of self-governance that includes formal rules and structures for decision-making, normative and cognitive underpinnings of identities and purposes, and specific practices. Studies of collegiality then, need to capture structures and rules as well as identities, norms, purposes and practices. Distinguishing between vertical and horizontal collegiality, we show how they balance and support each other. Universities are subject to mixed modes of governance related to the many tasks and missions that higher education and research is expected to fulfill. Mixed modes of governance also stem from reforms based on widely held ideals of governance and organization. We examine university reforms and challenges to collegiality through the lenses of three ideal types of governance – collegiality, bureaucracy and enterprise – and combinations thereof.
10.1108/S0733-558X20230000086001; 10.1108/S0733-558X20230000086001; University Collegiality and the Erosion of Faculty Authority; EBP099697246